56.5L: Late‐News Paper: All‐Printed Oxide Thin Film Transistor Arrays for High Resolution Active Matrix. Issue 1 (1st July 2013) - Matsumoto, Shinji; Nakamura, Yuki; Arae, Sadanori; Sone, Yuji; Hirano, Yukiko; Abe, Mikiko; Saotome, Ryohichi; Ueda, Naoyuki; Yamada, Katsuyuki
Abstract We have demonstrated all‐printed oxide TFT arrays for 100 ppi RGB active matrix fabricated by inkjet printing and spin coating without photolithography and mask process. The average mobility of TFTs was 7.49 ± 1.67 cm2/Vs on a thermally oxidized SiO2 /Si substrate. Moreover, in the case of using of a printed oxide high‐k gate insulator and an n‐type doped active layer on a glass substrate, the average mobility of all‐printed oxide TFTs was 2.54 ± 0.32 cm2/Vs.